Selective Hydrogenation of CO2 to Ethanol over Cobalt Catalysts - Wang, Lingxiang; Wang, Liang; Zhang, Jian; Liu, Xiaolong; Wang, Hai; Zhang, Wei; Yang, Qi; Ma, Jingyuan; Dong, Xue; Yoo, Seung Jo; Kim, Jin‐Gyu; Meng, Xiangju; et al. (Angewandte Chemie International Edition, 2018)
Methods for the hydrogenation of CO2 into valuable chemicals are in great demand but their development is still challenging. Herein, we report the selective hydrogenation of CO2 into ethanol over non‐noble cobalt catalysts (CoAlOx), presenting a significant advance for the conversion of CO2 into ethanol as the major product. By adjusting the composition of the catalysts through the use of different prereduction temperatures, the efficiency of CO2 to ethanol hydrogenation was optimized; the catalyst reduced at 600 ° gave an ethanol selectivity of 92.1 % at 140 °C with an ethanol time yield of 0.444 mmol g−1 h−1. Operando FT‐IR spectroscopy revealed that the high ethanol selectivity over the CoAlOx catalyst might be due to the formation of acetate from formate by insertion of *CHx, a key intermediate in the production of ethanol by CO2 hydrogenation. Just ethanol: CO2 was selectively hydrogenated into ethanol over non‐noble cobalt catalysts (CoAlOx). By adjusting the composition of the catalysts through the use of different prereduction temperatures, the efficiency of the reaction was optimized to give an ethanol selectivity of 92.1 % at 140 °C with an ethanol time yield of 0.444 mmol g−1 h−1. The high ethanol selectivity might be due to the formation of acetate from formate by *CHx insertion.